Conducting an Interview in Qualitative Research: The Modus Operandi - Elhami, Ali; Khoshnevisan, Babak (Mextesol journal, 2022)
Qualitative inquiry is an effective way to explore the perceptions of participants and unlock their experiences. In social science research (e.g., applied linguistics, sociology, sociolinguistics, psychology, psycholinguistics), there is a strong tendency among qualitative researchers to collect their required data through interviewing. Interviews are useful tools to glean the related data from the participants, and different types of interviews are commonly used to delve into the participants' perceptions. In this study, we address three types of interviews (structured, semi-structured, and unstructured), and compare them in detail. In addition, we focus on effective ways to form questions, offer a brief review of qualitative sampling, and provide guidelines for conducting an interview in qualitative studies. Finally, two examples of interviews with different structures are put forth to explore the process and to compare them. Having done this, we will juxtapose both the process and content to explore different types of questioning during the process of an interview. This study suggests the potential differences among different types of interviews. It also suggests how to select the best type of interview to collect the required data based on the nature of the study and research questions.